EXCAVATION, ANALYSIS AND INTERPRETATION OF AN EARLY BRONZE AGE ROUND BARROW AT GUITING POWER,... GLOUCESTERSHIRE - MARSHALL, ALISTAIR (ARCHAEOPRESS, 2020)
This volume covers the full excavation, analysis and interpretation of two early Bronze Age round barrows at Guiting Power in the Cotswolds, a region where investigation and protection of such sites have been extremely poor, with many barrows unnecessarily lost to erosion, and with most existing excavation partial, and of low quality.